1988
DOI: 10.1159/000128743
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Polyester Arterial Grafts Coated with Albumin: The Role and Importance of Cross-Linking Agents

Abstract: Previous in vitro studies have predicted that the type of chemical used to crosslink albumin-coated polyester arterial prostheses may influence the rate of bioerosion of the albumin layer in vivo. This study has confirmed that the healing process of this type of compound prosthesis does indeed depend on the nature and concentration of the cross-linking agent used. Four series of implantations in the thoracic aorta of dogs for scheduled periods for 4 h up to 6 months were conducted using 1.6% glutaraldehyde, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…To overcome these problems, collagen has been cross-linked by a variety of agents-a subject of much recent research to find methods of preventing rapid absorption by the body [4]. However, these methods suffer from the problem that the residual catalysts, initiators and unreacted or partially reacted cross-linking agents used can be toxic or cause inflammatory responses if not fully removed or, simply, not cost-effective or practical at the large scale [5][6][7]. As a consequence, research continues to find alternative methods to stabilise collagen which are natural, milder, efficient and more practical.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, collagen has been cross-linked by a variety of agents-a subject of much recent research to find methods of preventing rapid absorption by the body [4]. However, these methods suffer from the problem that the residual catalysts, initiators and unreacted or partially reacted cross-linking agents used can be toxic or cause inflammatory responses if not fully removed or, simply, not cost-effective or practical at the large scale [5][6][7]. As a consequence, research continues to find alternative methods to stabilise collagen which are natural, milder, efficient and more practical.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerized microaggregates of albumin can serve as agents for radiocontrast and ultrasonic imaging of the circulatory system [11]. Albumin is also used to coat prosthetic blood vessel grafts and vascular catheters to passivate these surfaces so as to minimize platelet aggregation and thrombotic consequences [11,110,111,112,113,114].…”
Section: Strategiesmentioning
confidence: 99%
“…For the impregnation of vascular grafts, mixtures of heparin(oids) and collagen, albumin, or proteins with an RGD sequence, have been the subject of many investigations (20). Guidoin et al (21,22) for instance, who compared different sealants for vascular prostheses, observed that the healing process of albuminated grafts was comparable to preclotted controls. However, contrary to collagen-impregnated grafts, tissue ingrowth of albuminated Dacron prostheses in pigs was limited (23).…”
Section: Introductionmentioning
confidence: 99%